2017
DOI: 10.1016/j.mib.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the holobiont: the interdependence of plants and their microbiome

Abstract: The holobiont is composed by the plant and its microbiome. In a similar way to ecological systems of higher organisms, the holobiont shows interdependent and complex dynamics [1,2]. While plants originate from seeds, the microbiome has a multitude of sources. The assemblage of these communities depends on the interaction between the emerging seedling and its surrounding environment, with soil being the main source. These microbial communities are controlled by the plant through different strategies, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
153
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(161 citation statements)
references
References 80 publications
4
153
0
4
Order By: Relevance
“…In this study, we identified ecological mechanisms that drive the composition and structure of the root mycobiome across a large‐scale environmental gradient in typical European temperate forests. There is now growing awareness that microbial assemblages fulfil important functions linking physiological and biogeochemical processes in forest ecosystems systems (Agler et al., ; Peay et al., ; Sánchez‐Cañizares et al., ; Vandenkoornhuyse et al., ). Our findings underpin that the taxonomic structures of RAMs in temperate forests are shaped by the biogeographic environment and host influence, while their trophic composition is stable across a large range of conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified ecological mechanisms that drive the composition and structure of the root mycobiome across a large‐scale environmental gradient in typical European temperate forests. There is now growing awareness that microbial assemblages fulfil important functions linking physiological and biogeochemical processes in forest ecosystems systems (Agler et al., ; Peay et al., ; Sánchez‐Cañizares et al., ; Vandenkoornhuyse et al., ). Our findings underpin that the taxonomic structures of RAMs in temperate forests are shaped by the biogeographic environment and host influence, while their trophic composition is stable across a large range of conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the holobiont hypothesis, the existence of plants in their environment requires a dedicated functional microbiome (Agler et al, 2016;Barbi et al, 2016;Sánchez-Cañizares, Jorrín, Poole, & Tkacz, 2017). In this context, the remarkable constancy of the trophic composition of the RAMs implies that temperate forests attract fungal assemblages that entail functional resilience under a certain range of climatic and edaphic conditions.…”
Section: The Dominance Of Mycorrhizal Fungi In Rams Of Fagaceae Andmentioning
confidence: 99%
“…A vast diversity of microorganisms colonize all organs of plants; these microorganisms constitute the plant microbiome and play an integral role in plant growth and health (Berg, Rybakova, Grube, & Koberl, ; Mendes et al., ; Rybakova et al., ; Sánchez‐Cañizares, Jorrín, Poole, & Tkacz, ). Recently, great efforts have been made to understand the plant microbiome, and the microbiota diversity of different tissues and developmental stages has been described for many plants, including major crops such as rice (Edwards et al., ), maize (Peiffer et al., ), barley (Bulgarelli et al., ), and soybean (Han et al., ; Liu et al., ; Sugiyama, Ueda, Takase, & Yazaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great efforts have been made to understand the plant microbiome, and the microbiota diversity of different tissues and developmental stages has been described for many plants, including major crops such as rice (Edwards et al, 2015), maize (Peiffer et al, 2013), barley (Bulgarelli et al, 2015), and soybean (Han et al, 2017;Liu et al, 2017;Sugiyama, Ueda, Takase, & Yazaki, 2014). Plant microbiota are hyper-diverse and highly dynamic throughout the life history of plants (Peiffer et al, 2013;Sánchez-Cañizares et al, 2017). However, the overwhelming majority of studies have focused on bacterial communities and on the microbiota associated with roots (rhizosphere) and above-ground plant parts (phyllosphere).…”
Section: Introductionmentioning
confidence: 99%
“…Holobionts have been described among many and far-related groups of living beings, such as plants (for review see: Vandenkoornhuyse et al 2015;Sanchez-Canizares et al 2017), algae (Egan et al 2012), insects (for review see: Guerrero et al 2013;Minard et al 2013;Berlanga and Guerrero 2016), corals (Vezzulli et al 2013; for review see: Thompson et al 2015;van de Water et al 2018), and even humans (Postler and Ghosh 2017). In this landscape, protists are under-represented, even though they are highly diverse and environmentally widespread (Šlapeta et al 2005;Foissner 2006;Weisse 2008), and known for their association with a wide range of other microorganisms (Molmeret et al 2005;Horn 2008;Ohkuma 2008;Schmitz-Esser et al 2010; for review see: Gast et al 2009;Görtz 2010;Nowack and Melkonian 2010;Schweikert et al 2013;Scheid 2014).…”
Section: Introductionmentioning
confidence: 99%